2017
DOI: 10.1037/apl0000169
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sleep and work: A meta-analysis.

Abstract: Sleep has tremendous importance to organizations because of its relationship with employee performance, safety, health, and attitudes. Moreover, sleep is a malleable behavior that may be improved by individual and organizational changes. Despite the consequential and modifiable nature of sleep, little consensus exists regarding its conceptualization, and how the choice of conceptualization may impact relationships with organizational antecedents and outcomes. To offer a stronger foundation for future theory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
317
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(355 citation statements)
references
References 261 publications
(236 reference statements)
22
317
2
Order By: Relevance
“…Empirical research has shown that interpersonal conflicts may be associated with increased sleep disturbance (Brissette and Cohen 2002). A recent meta-analysis on work conditions and sleep (Litwiller 2014) reported a significant association between sleep quality and workplace bullying (q = -0.23, k = 3), and between sleep quality and workplace violence (q = -0.20, k = 2). A recent systematic review on social stressors and sleep found 14 studies (Pereira et al in press), ten of which reported correlations between these variables.…”
Section: Social Stressors At Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Empirical research has shown that interpersonal conflicts may be associated with increased sleep disturbance (Brissette and Cohen 2002). A recent meta-analysis on work conditions and sleep (Litwiller 2014) reported a significant association between sleep quality and workplace bullying (q = -0.23, k = 3), and between sleep quality and workplace violence (q = -0.20, k = 2). A recent systematic review on social stressors and sleep found 14 studies (Pereira et al in press), ten of which reported correlations between these variables.…”
Section: Social Stressors At Workmentioning
confidence: 97%
“…However, other than work-family conflict, recovery during Sundays has not received much attention so far, although impeded recovery processes are said to be the crucial link in the development of ill-health in the long run (Geurts and Sonnentag 2006). Sleep plays a particularly prominent role in the research on recovery; studies have shown that work-related stressors are positively linked to sleep impairments (e.g., Ekstedt et al 2006;Lallukka et al 2011;Litwiller 2014) and that sleep impairments are positively linked to ill-health (e.g., Drake et al 2005). In a recent study, healthy men and women received viral exposure; it was tested whether sleep, measured by actigraphy, predicted the incidence of colds (Prather et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…First, many studies examined the consequences of workload for well-being (Alarcon, 2011;Ilies et al, 2010). Third, morning wellbeing might be closely related to sleep quality (Litwiller, Snyder, Taylor, & Steele, 2017;Scott & Judge, 2006). Thus, relationships between workload anticipation and nextmorning well-being might be due to high experienced workload.…”
Section: Control Variablesmentioning
confidence: 99%
“…The psychophysiological activation that occurs as a response to social exclusion, however, should be incommensurate with the deactivation that is a main characteristic of sleep. A meta-analysis on work conditions and sleep reported a significant association between sleep quality and workplace bullying (Rho=−0.23, k=3), and between sleep quality and workplace violence (Rho=−0.20, k=2)29 ) . A recent systematic review on adverse social job characteristics and sleep found 14 studies, ten of which reported correlations20 ) .…”
Section: Introductionmentioning
confidence: 99%